International co-operation in health - McKee, Martin; Garner, Paul (Paul Adrian); Stott, Robin (Oxford : Oxford University Press, 2001)
Primarily about how international collaboration can promote the health of the world's population and help tackle current and emerging public health problems, this volume provides examples of how and why international co-operation can help health care.
Description based on print version record.
Includes bibliographical references and index.
Keywords: World health; Public health -- International cooperation